Nanoliposomal irinotecan with fluorouracil and folinic acid in patients with unresectable or recurrent pancreatic cancer: a multicenter observational study (NAPOLEON-2) - T. Shirakawa; M. Shimokawa; T. Otsuka; Y. Shinohara; K. Toyodome; W. Kusano; J. Nakazawa; T. Kodama; M. Kawahira; H. Shimokawa; T. Koike; F. Koga; et al. (ESMO Gastrointestinal Oncology)
Background: Nanoliposomal irinotecan with fluorouracil and folinic acid (NFF) is a standard second- or later-line regimen after gemcitabine-based therapy for patients with unresectable or recurrent pancreatic cancer (urPC). However, limited prospective clinical data on the efficacy and safety of NFF in a real-world setting have been presented. Therefore, we conducted this observational, real-world study to investigate the efficacy and safety of NFF. Patients and methods: We collected prospective data of urPC patients treated with NFF in 17 hospitals in Japan from 2021 to 2023. The primary endpoint was overall survival (OS). Secondary endpoints were overall response rate, disease control rate, progression-free survival, dose intensity, and adverse events (AEs). Results: NFF was administered to 150 patients with a mean age of 72 years. The median follow-up period was 7.2 months. All patients had previously received gemcitabine-based therapy. The median OS was 7.8 months; median progression-free survival was 3.7 months; median overall response rate was 11%; and median disease control rate was 56%. Median relative dose intensity was 72.7% with nanoliposomal irinotecan and 79.4% with fluorouracil. Grade 3/4 hematological and nonhematological AEs occurred in 52 and 70 patients, respectively. Neutropenia (28%) and anorexia (19%) were common grade 3/4 AEs. Subanalysis of patients with second-line and third- or later-line therapy demonstrated no significant difference in OS (7.4 versus 7.8 months, respectively; P = 0.88). Integrated analysis of the prospective and retrospective phases of the study showed that median OS was 8.0 months. Conclusions: NFF has an appropriate efficacy and safety profile and is a candidate for second- or later-line therapy for urPC.